Unemployment as a Psycho-Social Stressor during Economic Recession. Well-being in employed vs. unemployed workers in Iceland. - Klargaard, Sólja Katrina, 1978- (2011)
The level of deprivation of latent and manifest functions of employment (Jahoda, 1981) during economic recession and high local unemployment was explored with resulting health-related outcomes. Strain and stress factors in employed vs. unemployed workers were compared, with age as a constant (35-45 years). Results indicated no significant group-differences on latent deprivation, quality of sleep, circadian rhythm, napping or depression; on the other hand, manifest or financial deprivation and health-related quality of life differed significantly among groups of employed and unemployed workers. Locus of control and gender were found to be significant mediators in the relation between stress and strain variables.